2020
DOI: 10.1097/tp.0000000000003178
|View full text |Cite
|
Sign up to set email alerts
|

Proton Pump Inhibitors, But Not H2-receptor Antagonists, Are Associated With Incident Fractures Among Kidney Transplant Recipients

Abstract: Background. Fractures are a common and burdensome problem among kidney transplant recipients (KTRs). Proton pump inhibitors (PPIs) are frequently used after kidney transplantation and have been associated with increased fracture risk in the general population. This study aimed to determine whether PPI use is associated with incidence of major fractures in KTRs. Methods. Using the Wisconsin Allograft Recipient Database, we identified 155 KTRs with a majo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
15
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 32 publications
0
15
1
Order By: Relevance
“…The lack of a significant association between PPI use and BMD decrease is in apparent conflict with previous studies that linked PPI use with greater risk of fractures in both the general population [11,12,14,26,27] and KTRs [16,17]. A meta-analysis involving 18 relevant observational studies in the general population showed PPI use modestly increased the risk of hip, spine, and any osteoporotic fracture [28].…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…The lack of a significant association between PPI use and BMD decrease is in apparent conflict with previous studies that linked PPI use with greater risk of fractures in both the general population [11,12,14,26,27] and KTRs [16,17]. A meta-analysis involving 18 relevant observational studies in the general population showed PPI use modestly increased the risk of hip, spine, and any osteoporotic fracture [28].…”
Section: Discussionmentioning
confidence: 91%
“…Roughly half of KTRs receive PPIs or histamine-2 receptor antagonists (H2RAs) prophylaxis for gastric complications following transplantation, and some recipients remain on these therapies for years after transplantation [10]. Observational studies have found an association between high dose and long-term PPI therapy and fracture in the general population and in KTRs [11][12][13][14][15][16][17]. Results of studies examining the association between PPIs and change in bone mineral density (BMD) in the general population have been inconsistent [18][19][20].…”
Section: Introductionmentioning
confidence: 99%
“…16,17 Other transplant studies have demonstrated associations between PPI use and hypomagnesemia, Clostridium difficile infections, iron deficiency anemia, and increased fracture risk. [18][19][20][21][22][23][24] However, these studies did not compare PPIs to H2RAs [18][19][20][21][22] and included relatively small cohorts. 23,24 Most studies comparing the impact of PPI or H2RA use on renal function posttransplant report outcomes up to a year posttransplant.…”
mentioning
confidence: 99%
“…[18][19][20][21][22][23][24] However, these studies did not compare PPIs to H2RAs [18][19][20][21][22] and included relatively small cohorts. 23,24 Most studies comparing the impact of PPI or H2RA use on renal function posttransplant report outcomes up to a year posttransplant. 14,15 Currently, the only study evaluating the effect of PPIs or H2RAs on long-term renal function demonstrated significantly worse kidney function in PPI treated patients but has not been published in full manuscript form.…”
mentioning
confidence: 99%
See 1 more Smart Citation